2010
DOI: 10.1111/j.1467-9221.2010.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Foundations of Ideological Divide: A Comparison of Women Members of Parliament and Women Voters in Italy

Abstract: Empirical research is crucial for understanding the personality foundations of political preferences in modern democracies. However, few studies have addressed the personality of top politicians using standard methods to assess basic traits and personal values. In the current research, traits and values of 106 female members of the Italian Parliament were assessed in accordance with the Five-Factor Model of personality and Schwartz's taxonomy. The same variables were measured in a sample of 864 voters taken fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 39 publications
7
41
0
1
Order By: Relevance
“…There are only a few studies of the personality traits of political elites based on validated, direct measures (Italy: Caprara, Barbaranelli, Consiglio, Picconi, & Zimbardo, ; Caprara, Francescato, Mebane, Sorace, & Vecchione, ; Germany: Best, ; United States: Constantini & Craik, ; Dietrich, Lasley, Mondak, Remmel, & Turner, ; Hanania, ; see also Hennessy, ; McConaughy, ). So far, no study of legislators has been undertaken in a Scandinavian country, and, to our knowledge, no one has examined personality differences both on the Big Five level and the aspect level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are only a few studies of the personality traits of political elites based on validated, direct measures (Italy: Caprara, Barbaranelli, Consiglio, Picconi, & Zimbardo, ; Caprara, Francescato, Mebane, Sorace, & Vecchione, ; Germany: Best, ; United States: Constantini & Craik, ; Dietrich, Lasley, Mondak, Remmel, & Turner, ; Hanania, ; see also Hennessy, ; McConaughy, ). So far, no study of legislators has been undertaken in a Scandinavian country, and, to our knowledge, no one has examined personality differences both on the Big Five level and the aspect level.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a subsequent study of female Italian members of parliament ( N = 103; response rate = 70%), elites differed significantly from female voters in all personality traits except Conscientiousness. Female MPs were more open, extraverted, agreeable, and emotionally stable (Caprara et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same trend was found in one recent study that used instead Schwartz's personal values questionnaire. Caprara, Francescato, Mebane, Sorace, and Vecchione () compared 106 women members of parliament and 864 voters using the Big Five questionnaire and Schwartz's basic values questionnaire. They investigated the extent to which differences in traits and values contribute to ideological orientation of politicians and voters of rival coalitions.…”
Section: Politics Of Presence Theory and Related Empirical Researchmentioning
confidence: 99%
“…The general idea is that the personality traits of a leader tend to affect their performance in political roles (Silvester et al, 2014), such as in terms of leading organization, making policies, and even connect with the people. Often employ an "at-a-distance" methodology to assess a political figure's personality, studies suggested that political roles might require the trait of extraversion and openness, with a little demand of neuroticism and conscientiousness (Caprara, Francescato, Mebane, Sorace, & Vecchione, 2010;Silvester et al, 2014). When we discuss personality, we are not just looking at the politician's abilities and strategies, but also the execution, their intention, and possibility of predicting the outcome of their effort in establishing social changes.…”
mentioning
confidence: 99%